2019
DOI: 10.4018/978-1-7998-1282-1.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Self-Directed Vocabulary Study: Towards Effective Design of OERs for Mobile Learning Environments

Abstract: Although open educational resources (OERs) can help bridge high-school – university vocabulary gaps, optimal utilization of OERs requires effective self-directed learning. This bi-national two-year study adopted a design-based research paradigm to collect Chinese university students' (n = 358) perceptions regarding design factors that support self-directed vocabulary learning in mobile learning environments (MLEs). Results showed that additional scaffolding after Year One in the form of L1 translations of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a similar vein, Barth et al (2020) exploring Chinese EFL students' attitudes and perceptions towards design factors supporting self-directed mobile-based vocabulary learning, found that scaffolding in the form of first language translation developed basic and high-frequency vocabulary learning in mobile learning environments. The findings further propose that in order to move mobile learning to mainstream education, students' capacity for self-directed learning need to be enhanced beforehand.…”
Section: Self-regulation In Vocabulary Learningmentioning
confidence: 95%
See 1 more Smart Citation
“…In a similar vein, Barth et al (2020) exploring Chinese EFL students' attitudes and perceptions towards design factors supporting self-directed mobile-based vocabulary learning, found that scaffolding in the form of first language translation developed basic and high-frequency vocabulary learning in mobile learning environments. The findings further propose that in order to move mobile learning to mainstream education, students' capacity for self-directed learning need to be enhanced beforehand.…”
Section: Self-regulation In Vocabulary Learningmentioning
confidence: 95%
“…That is, a quantitative longitudinal research design is adopted in this study to investigate EFL learners’ longitudinal trajectories and patterns of change in vocabulary learning. In addition, as the concept of self-regulation ( Zimmerman and Schunk, 2008 ), which refers to learners’ activating and sustaining planned self-generated thoughts, emotions, and activities to achive their learning goals ( Zimmerman, 2000 , 2008 ), has received considerable attention in the MALL context (e.g., García Botero et al, 2021 ), especially in mobile-based vocabulary learning context (e.g., Barth et al, 2020 ). EFL learners’ self-regulatory vocabulary learning changes over the 1-year MALL programme is also examined in the present study.…”
Section: Introductionmentioning
confidence: 99%